A towed submersible - Dunkley, William Rae (Not Specified, 2023)
One way to continuously scan the sea would be to tow a submarine vehicle that would cycle vertically in the water between set depths. Its period of vertical oscillation would be short compared with the changes in parameters to be measured, in this case long internal waves. It would carry continuously recording depth and temperature measuring instruments; if possible storing the results on a magnetic tape or paper drum or else transmitting the data to the towing vessel. It could be designed so that it was relatively independent of ship speed and self-contained so that it could operate unattended for long periods of the normal oceanographic surveys require regular stops for geological core samples to be taken or for sampling reversing bottles to be cast, and during these moments the vehicle could be hauled aboard and its recording sheets or power sources renewed as necessary. Accordingly a specification was determined in consultation with members of the Oceanography Department of the University for a suitable towed body (Table 1.1). Initially it was to carry temperature measuring devices, but it should have the possibility of extending this to carry instruments to measure pH, conductivity, etc.. The only published work at present concerning such a device is by Glover (2), who is developing an undulating plankton recorder for long distance towing with an oscillating wave length of 20 km. It is not very appropriate to make direct comparison with Glover's work since there local instabilities are damped out during the long, slow oscillations, whereas for a device with a much shorter wave period such local perturbations crucially affect the performance. A device with a relatively short undulation period for intense data collection would be a major advance in oceanographic recording techniques, and one that could have a wide variety of commercial applications.